2015
DOI: 10.5847/wjem.j.1920-8642.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of malaria: examination of the spleen, liver, and optic nerve sheath diameter

Abstract: BACKGROUND: Over 90% of all cases of malaria worldwide occur in Africa. Current methods of diagnosis are time and labor intensive, and could lead to delayed treatment. METHODS:In this study we investigated the effectiveness of measurements of spleen, liver, and optic nerve sheath diameter (ONSD) in identifying patients with malaria or severe malaria through the use of hand-held ultrasound devices. We recruited 40 adult patients with malaria and 16 adult control subjects at two hospitals in Mwanza, Tanzania. Ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Zha et al . developed a risk stratification protocol for malaria in an endemic area, using measurements of spleen, liver and optic nerve sheath diameter by a hand‐held ultrasound device . Murphy et al .…”
Section: Resultsmentioning
confidence: 99%
“…Zha et al . developed a risk stratification protocol for malaria in an endemic area, using measurements of spleen, liver and optic nerve sheath diameter by a hand‐held ultrasound device . Murphy et al .…”
Section: Resultsmentioning
confidence: 99%
“…Even though they are seen in other common pathological condition, imaging of the liver and spleen could be helpful as part of a diagnostic support in severe malaria. 21 ACT is the recommended drug of choice in anti-malarial treatment protocol across the globe. In this study, ACT showed significant (p value <0.000) improvement (near normal levels) of bilirubin and hepatic enzymes by day 4.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ultrasonography is not sensitive to lesions with low blood-flow perfusion or lack of blood supply. Therefore, examinations using CT and MRI for diagnosis are mainly adopted in clinical practice ( 11 ).…”
Section: Discussionmentioning
confidence: 99%